One size fits some: Analysing profitability, capital and liquidity constraints of custodian banks through the lens of the SREP methodology - Charles-Enguerrand Coste; Céline Tcheng; Ingmar Vansieleghem (European Central Bank (ECB), 2021)
Custodians play a key but discrete role in the global financial market infrastructure. In Europe, they are licensed as "credit institutions ", a legal requirement for European deposit-taking institutions, and therefore they face the same prudential requirements as "traditional" banks. However, their business model and risk profile are different from those of traditional banks since the core of their activity does not encompass balance sheet transformation and the associated risks.
Keywords: G15; G21; G28; L22; 330; bank; custodian; credit institution; prudential supervision